Artikulasi Identitas Wong Solo di Eks Enklave Surakarta: Konstruksi Bahasa dan Pemertahanannya - Sandi Sanjay; Danu Al Aziz Salim; Wirda Rohmah (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
This article explores how the identity of Wong Solo is expressed and maintained in the former areas of Surakarta through the use of language and its preservation. The research uses a literature review approach to examine the topic. The study is based on the idea that the cultural identity of the Surakarta community is formed not just by social activities and traditions, but also by the way people communicate, which reflects shared values, a sense of history, and a feeling of belonging. By looking at literature in the fields of linguistics, cultural anthropology, and local citizenship studies, the research identifies how the Surakarta dialect of Javanese plays a key role in reinforcing the identity of Wong Solo during times of fast social change. The study finds that language-based identity is shown through the words people choose, the way they speak, the rules of politeness, and the specific ways of speaking that are part of Surakarta society. However, factors like globalization, urban development, and influences from other cultures challenge the stability of this identity, especially among the younger population. Efforts to keep the language alive are seen in various cultural preservation projects, the revival of Javanese writing, local government actions, and increased community participation. The study argues that language is essential in keeping Wong Solo identity alive, while also acting as a place where tradition and modernity meet, shaping the changing identity of the former enclaves of Surakarta.